Hungarian Monitoring, 23 March 1990 . [Magyar rádiófigyelő], 1990. március 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Lithuania holds to its independence efforts - Estonian CP congress on arrangements to introduce multi-party system Domestic Affairs: - Investigation of putsch charges against Miklós Németh refused - Statements from Transylvania, reports Hungarian government's position - Elections: final day of campaigning, international press conference, election rallies, pupils on the election campaign Külpolitika: - Litvániában kitartanak a függetlenségi törekvések mellett - Az észt KP kongresszusa a többpártrendszer feltételeiről Belpolitika: - Németh Miklós puccskísérlet vádjával szemben megtagadták a nyomozást - Erdélyi jelentések, tudósítások; a magyar kormány állásfoglalása - Választás: a kampány zárónapja, nemzetközi sajtótájékoztató,választási gyűlések, kisiskolások a választást hadjáratról